Cardiac magnetic resonance strain as a predictor of clinical events in hypertrophic cardiomyopathy. (13th July 2021) - Martinez Vives, P; Cecconi, A; Vera, A; Nogales-Romo, T; Lopez-Melgar, B; Rojas-Gonzalez, A; Jimenez-Borreguero, LJ; Alfonso, F
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Hypertrophic cardiomyopathy (HCM) is a relatively prevalent condition associated with cardiovascular death and heart failure. Several tools are currently available to identify which HCM patients are at risk of developing these events. Purpose: We aimed to evaluate the association of new Tissue Tracking strain analysis by cardiac magnetic resonance (CMR) and the development of clinical events in patients with HCM. Methods: We prospectively analyzed 136 consecutive patients with HCM diagnosis (established according to current clinical practice guidelines) from January 2006 to October 2017. Heart failure hospital admissions and death on follow-up were included in a combined clinical outcome. CMR studies were performed following our predefined CMR protocol for HCM with 1.5T magnets. Cine images were obtained with standard, retrospectively gated, steady-state free-precession (SSFP) sequences in 2, 3 and 4 chambers views and in 10–15 contiguous short-axis slices covering the ventricles from the base to the apex, with breath holding.  The strain evaluation was performed by a commercially available Tissue Tracking analysis software, manually defining the endocardial border in short axis, 4, 3 and 2 chambers views and, after verifying adequate identification of the different structures, running the strain analysis (Figure 1, displaying myocardium identification by the strain analysis software). Results: Mean follow-up was 49 ± 45 months. Mean age was 61 ± 15.33 years old (p 0.024) and 31% of patients were women (p 0.01). 20% had atrial fibrillation (p 0.154). Mean ejection fraction was 69 ± 9.21% (p 0.762) and mean HCM-SCD (hypertrophic cardiomyopathy sudden cardiac death) risk score was 2.20 ± 1.35 (p 0.885). Mean global radial systolic strain rate (GRSsr) was -1, 33 ± 0.59 s-1 (p 0.083). During follow-up, 12 heart failure hospital admissions and 14 death from any cause were registered. GRSsr showed an area under de ROC curve of 0.63 (95% confidence interval -CI- 0.51 – 0.75) predicting clinical events. The value of 1.40 s−1 was selected as the best sensitivity/specificity cutoff point. Three variables (sex, age, and previous history of atrial fibrillation) were chosen (through the allsets method) and included as adjusting variables together with <1, 40 s−1/≥1.40 s−1 in a multivariate Cox's regression model (p 0.002; AIC 99.7; Harrell C index 0.82). Patients with GRSsr <1.40 s−1 showed more clinical evens on follow-up vs those with GRSsr ≥1.40 s−1 (adjusted HR 6.57; 95% CI 2.01 – 21.49; p 0.002; Figure 2, displaying Kaplan-Meier survival estimates). Conclusions: A GRSsr <1.40 s−1 emerges as a novel independent predictor of worse clinical outcomes in patients with HCM and preserved ejection fraction.